2021
DOI: 10.1590/1807-1929/agriambi.v25n12p819-825
|View full text |Cite
|
Sign up to set email alerts
|

Root distribution of cactus pear genotypes under different soil water replacement levels

Abstract: Knowledge of the cactus pear root distribution system can improve management of the plant by defining the areas of soil best suited to fertilizer application and the installation of soil moisture sensors under irrigation. Thus, the aim of the present study was to assess the root distribution of cactus pear genotypes under different water replacement levels. To that end, a field experiment was conducted in a randomized block design, using genetic material from two cactus pear genotypes (Opuntia fícus-indica Mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…The highest RDL values for very fine roots in plots irrigated with high-salinity water at 33% ETo with a 3-d II and at 50% ETo with a 2-d II formed a group, while the remaining treatments were grouped with lower RDL values (Table 4). Castro et al (2021) also found no differences in RLD of small root class with an increase in the percentage of soil water replacement level; however, they found an increase in RLD of very fine and fine root classes up to the irrigation level of 75% of ETo.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The highest RDL values for very fine roots in plots irrigated with high-salinity water at 33% ETo with a 3-d II and at 50% ETo with a 2-d II formed a group, while the remaining treatments were grouped with lower RDL values (Table 4). Castro et al (2021) also found no differences in RLD of small root class with an increase in the percentage of soil water replacement level; however, they found an increase in RLD of very fine and fine root classes up to the irrigation level of 75% of ETo.…”
Section: Resultsmentioning
confidence: 85%
“…Castro et al (2021) also found a higher concentration of all classes of 'Gigante' and 'Miuda' forage cactus pear's roots at a distance of up to 0.20 m from the base of the plant and at a depth of 0.10 to 0.25 m. The results of these authors corroborate those obtained in the present study, with the concentration of the cactus pear root system in the first 0.15 m deep and at shorter distances from the plant. This consolidates the technical recommendations for the crop, such as applying fertilizers close to the plant to increase nutrient-use efficiency by improving nutrient uptake and utilization by plants.1 ** -Significant at p ≤ 0.01 and * -Significant at p ≤ 0.05 by the t test.…”
mentioning
confidence: 99%